LAMBERT–EATON MYASTHENIC SYNDROME–RESULTS FROM THE BNSU SURVEY. Issue 11 (9th October 2013) - Maddison, Paul; Gozzard, Paul
Abstract : Lambert–Eaton myasthenic syndrome (LEMS) is an autoimmune, presynaptic disorder of neuromuscular transmission characterised by proximal limb weakness, autonomic disturbance and depressed tendon reflexes with post–tetanic potentiation. Approximately 50% of patients with LEMS have an underlying small–cell lung cancer (SCLC), and the prevalence of LEMS in SCLC populations is 3–5%. It is thought that patients with SCLC–LEMS may survive longer that patients with SCLC alone, although there have been no prospective unbiased studies to confirm this. Specific antibodies to P/Q–type voltage–gated calcium channels (VGCC) at the motor nerve terminal are found in 85–90% of cases. LEMS is a rare disorder with a rising incidence of approximately 0.75 per million in European populations, and prevalence approaching 3.5 per million. With approximately 7500 new cases of small–cell lung cancer diagnosed in the UK per annum, it ought to be expected that between 225 and 375 new SCLC–LEMS diagnoses should be made each year. Thus, it is likely that the condition is being missed or misdiagnosed: previous data from UK and Dutch patients suggest that over half of all LEMS patients are initially misdiagnosed. The aims of the LEMS British Neurological Surveillance Unit (BNSU) survey was three–fold: firstly, to allow us to collect data on LEMS patients to establish a cohort of cases prospectively in order to determine, without bias, whether SCLC–LEMS patients survive longer than patients with SCLC without LEMS; secondly, to collect large serum samples to store as part of a LEMS biobank; and thirdly, to use these samples to design assays to predict the antigenic target in sero–negative cases, to develop a non–radioisotope cell–based assay for VGCC antibodies, and to use in future studies to determine whether LEMS IgG can alter SCLC cellular proliferation in vitro. Between March 2010 and January 2013, we were notified of 40 new LEMS cases via the BNSU of the Association of British Neurologists. Of these, 21 (52.5%) LEMS patients returned a signed consent to us, and enrolled in the study. Clinical details have been obtained from 16 (76%) patients, so far, and large serum samples from five. Only four LEMS patients (4/16, 25%) are known to have an associated tumour (all SCLC), 8/16 (50%) are autoimmune, with over 3 years' follow–up, and four are still being screened for malignancy, soon after their initial LEMS diagnosis. During the same data collection period, the authors enrolled a further four LEMS patients from ongoing studies in the East Midlands, two of whom had an associated SCLC. With an expected annual incidence of at least 45 new LEMS cases per year, this study highlights the significant under–reporting, and missed diagnosis of LEMS. It is possible that many patients with paraneoplastic LEMS remain under the care of oncologists, and are never seen by neurologists: many more cases of paraneoplastic SCLC–LEMS are not being recognised, or reported to neurologists. The clinical details and serum samples obtained from LEMS patients via the BNSU have been invaluable in providing source material for ongoing clinical and laboratory studies.